Portable evaluation of obstructive sleep apnea in adults: A systematic review. (April 2023) - Khor, Yet H.; Khung, Su-Wei; Ruehland, Warren R.; Jiao, Yuxin; Lew, Jeremy; Munsif, Maitri; Ng, Yvonne; Ridgers, Anna; Schulte, Max; Seow, Daniel; Soon, William; Churchward, Thomas; et al.
Abstract: Obstructive sleep apnea (OSA) is a significant healthcare burden affecting approximately one billion people worldwide. The prevalence of OSA is rising with the ongoing obesity epidemic, a key risk factor for its development. While in-laboratory polysomnography (PSG) is the gold standard for diagnosing OSA, it has significant drawbacks that prevent widespread use. Portable devices with different levels of monitoring are available to allow remote assessment for OSA. To better inform clinical practice and research, this comprehensive systematic review evaluated diagnostic performances, study cost and patients' experience of different levels of portable sleep studies (type 2, 3, and 4), as well as wearable devices and non-contact systems, in adults. Despite varying study designs and devices used, portable diagnostic tests are found to be sufficient for initial screening of patients at risk of OSA. Future studies are needed to evaluate cost effectiveness with the incorporation of portable diagnostic tests into the diagnostic pathway for OSA, as well as their application in patients with chronic respiratory diseases and other comorbidities that may affect test performance.